Exploring the genetic resources of yam in the Democratic Republic of Congo: implications for breeding - Adejumobi, Idris; Adewumi, Adeyinka Saburi; Ouattara, Fatim; Olatunde, Esther; Adheka, Joseph; Onautshu, Didy; Kayondo, Siraj Ismail; Alaba, Oluwafemi; Mushoriwa, Hapson; Agre, Paterne Angelot (Frontiers in Horticulture, 2024)
IntroductionLandrace accession of yam species in the Democratic Republic of Congo (DRC) represents a valuable genetic resource for yam breeding programs. These accessions possess traits such as stress resilience and desirable food quality attributes that can be introduced into modern yam varieties. By analyzing the genetic diversity, identifying quantitative trait loci (QTLs) linked to key traits, and the genetic merits of these landraces, we can identify promising genetic markers for breeding programs aimed at improving yam production in DRC.Materials and methodsWe analyzed 181 yam accessions from the Democratic Republic of Congo (DRC), representing six species commonly cultivated by farmers and their wild relatives. These accessions were genotyped using 10,621 DArTseq SNP markers and characterized for key productivity and food quality traits.Results and discussionPopulation structure analysis revealed six distinct genetic groups within the yam accessions. Genome-wide association studies (GWAS) identified 14 SNP markers associated with five key traits, suggesting the accessions’ potential as a valuable genetic resource. Further dissection of their genetic merits in yam breeding using the Genomic Prediction of Cross Performance (GPCP) allowed the identification of several accessions with high crossing merit for multiple traits. Genomic Prediction of Cross Performance (GPCP) identified 20 accessions with high crossing merit (>2).ConclusionsThese accessions demonstrate favorable genetic combinations for multiple traits, making them promising progenitors for developing segregating populations with improved characteristics. These findings highlight the potential of these accessions to contribute to genetic improvement in yam breeding programs in the DRC, focusing on traits such as productivity and food quality.